Handbook of Intercultural Communication and Cooperation Basics and Areas of Application - Thomas, Alexander; Kinast, Eva-Ulrike; Schroll-Machl, Sylvia (2010)
The ability to communicate with people from diverse cultural backgrounds is becoming increasingly important. Many employers consider intercultural competence to be a key criterion for selecting qualified candidates. The authors discuss practical approaches for designing and conducting intercultural trainings, methodology, and evaluation procedures based on current research. They explore the intercultural factor within corporations particularly as it relates to human resource development, negotiating, dealing with conflict, and project management. Thoughts on developing an overall strategy for interculturality round off this handbook.